2000
DOI: 10.1103/physrevb.61.15738
|View full text |Cite
|
Sign up to set email alerts
|

Disordered photonic crystals understood by a perturbation formalism

Abstract: Photonic band gaps in disordered two-dimensional photonic crystals are investigated for two typical types of randomness: cylinder site displacements ͑site randomness͒ and cylinder radius variations ͑size randomness͒. The plane-wave expansion method with a supercell technique is applied to calculate the density-of-states ͑DOS͒ for the disordered photonic crystals. In particular, numerical simulations on the DOS for square and triangular lattices of dielectric cylinders in air with the E-polarization mode show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 33 publications
2
45
1
1
Order By: Relevance
“…In fact, recent work on two-dimensional ͑2D͒ disordered photonic crystal 17 demonstrated that the higher band gap is far more sensitive to the site and size randomness than the ground band gap. Although this is apparent from a simple physical argument, our interest here is to investigate how fragile the gap in inverse-opal crystal could be in the presence of disorder.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent work on two-dimensional ͑2D͒ disordered photonic crystal 17 demonstrated that the higher band gap is far more sensitive to the site and size randomness than the ground band gap. Although this is apparent from a simple physical argument, our interest here is to investigate how fragile the gap in inverse-opal crystal could be in the presence of disorder.…”
mentioning
confidence: 99%
“…Similar behavior was found in 2D cases. 17 It can be argued qualitatively that varying the size of the sphere means changing the filling fraction, while the fraction does not change when displacing spheres from lattice sites. Thus, the size randomness reduces the gap size more significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been done on the effects of disorder on band-gap size and density of states (DOS) of photonic crystals as well as on the transmission in these crystals (see, for example, Refs. [25][26][27]). A common approach is to introduce a random disorder on the location or geometric features of the inclusions (such as cylinders or spheres) across several cells, and to subsequently solve for the band structure, DOS, or transmission performance, of a "supercell" that comprises the perturbed cells.…”
Section: Geometric Disorder Sensitivitymentioning
confidence: 99%
“…PhC cavities and the associated modal confinement can be achieved by introducing a defect in the periodic lattice such as removing a hole from a 2D lattice of airholes, which leads to a localized state in the photonic bandgap. An alternative is a defect-free PhC cavity, i.e., a cavity in which none of the air holes is removed from the periodic lattice [16][17][18][19]. Rather, such cavities result in PhCs made of photosensitive chalcogenide glass [20], by the introduction of nanodiamonds into airholes [21], and in PhCs with airholes with graded radii [16,22].…”
Section: Introductionmentioning
confidence: 99%